Making Sense as a Cultural Practice Historical Perspectives - Rogge, Jörg (Mainzer Historische Kulturwissenschaften, 2013)
In the cultural and social formations of the past, practices exist for the generation and integration of moments having and giving sense with the objective of strengthening the cultural and social cohesion. Such practices and processes have a constructive character, even if this is not always the intention of the actors themselves. As the production of sense is one of the central fields of action of cultural and political practice, the articles examine with an interdisciplinary perspective how, in different contexts, the construction of sense was organized and implemented as a cultural practice